KEARIFAN LOKAL TABOT SEBAGAI SUMBER BELAJAR SEJARAH DI SMA: SEBUAH ANALISIS RELEVANSI - Een Syaputra; Irwan Satria (Sosio-Didaktika: Social Science Education Journal, 2020)
Tabot is the local wisdom of Bengkulu whose existence plays an important role in society. As a pearl of local wisdom, the values contained in Tabot tradition are very important to be internalized to students as young people. One of the strategies is through integrated Tabot local wisdom in history learning in senior high school, especially as a source of learning. The purposes of this research are to describe Tabot local wisdom and analyze the relevance of Tabot local wisdom as a source of history learning in senior high school. This research was conducted with library research. The research steps undertaken are: 1) preparing tools and equipment; 2) compiling a working bibliography; 3) arranging research time; 4) reading and making research notes, and 5) concluding and analyzing the results of the research. The results of the research showed that: 1) Tabot tradition in one tradition that has been entrenched in Bengkulu, whose existence has been going on for hundreds of years. As a tradition that breathes Islam, Tabot tradition in Bengkulu has experienced acculturation with a local culture so that it can survive until now. Also, the Tabot tradition is a tradition that is rich in values, especially religious and social values such as cooperation, brotherhood, social care, responsibility, and others; 2) Tabot local wisdom is very relevant to be used as a source of history learning in senior high school, especially on three Basic Competences, namely Basic Competence 3.7. and Basic Competence 3.8. for X classes and Basic Competence 3.2. for the XI class.